2017
DOI: 10.1177/000313481708300421
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Characteristics Affect Consent and Conversion Rates for Potential Organ Donors

Abstract: Consent and conversion rates of potential organ donors in the United States need to be maximized to match the number of individuals awaiting organ donation. Studies to date have not focused on characteristics of centers with better outcomes. We performed an 8-year (2006–2014) retrospective study of our local organ procurement organization database. We categorized hospitals in our region as academic centers versus nonacademic centers, trauma centers versus nontrauma centers, and large (≥400 beds) centers versus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…Supporting our findings, a study by Ali et al [ 16 ] revealed that small academic trauma centers had significantly higher consent rates than large, nontrauma, or nonacademic centers. Another previous study similarly demonstrated that both nontransplant and nonurban centers had higher conversion rates [ 15 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Supporting our findings, a study by Ali et al [ 16 ] revealed that small academic trauma centers had significantly higher consent rates than large, nontrauma, or nonacademic centers. Another previous study similarly demonstrated that both nontransplant and nonurban centers had higher conversion rates [ 15 ].…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have examined the effects of hospital characteristics on consent rate. This research has revealed that consent rates across academic centers were 9% higher than for non-academic centers, while trauma centers exhibited higher family consent rates by 4% to 7.7% compared to non-trauma centers [ 14 - 16 ].…”
Section: Introductionmentioning
confidence: 99%